2020
DOI: 10.3390/ijms21218318
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 Genetic Variants Are Associated with Altered Clinical Outcome and Susceptibility to Gram-Positive Infections in Patients with Sepsis

Abstract: Background: Previous studies have reported the fundamental role of immunoregulatory proteins in the clinical phenotype and outcome of sepsis. This study investigated two functional single nucleotide polymorphisms (SNPs) of T cell immunoglobulin and mucin domain-containing protein 3 (TIM-3), which has a negative stimulatory function in the T cell immune response. Methods: Patients with sepsis (n = 712) were prospectively enrolled from three intensive care units (ICUs) at the University Medical Center Goettingen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Finally, and in support of the aforementioned delineation of immune effector functions on bacterial infection and systemic inflammation, as therapeutic strategy, preclinical and clinical studies assessing the safety of neutralising checkpoint receptors including PD-1 and TIM3 in sepsis and septic shock have been used and show promising results [26,57,58,59,60]. Taking this promising data plus the knowledge that preventing the detrimental impact of cytokine targeting remains a challenge, acting on immunoregulatory switches that orchestrate immune effector functions may be an alternative, possibly more favourable approach.…”
Section: Gut Liver Axis and Systemic Inflammation In Alcoholic Liver Diseasementioning
confidence: 99%
“…Finally, and in support of the aforementioned delineation of immune effector functions on bacterial infection and systemic inflammation, as therapeutic strategy, preclinical and clinical studies assessing the safety of neutralising checkpoint receptors including PD-1 and TIM3 in sepsis and septic shock have been used and show promising results [26,57,58,59,60]. Taking this promising data plus the knowledge that preventing the detrimental impact of cytokine targeting remains a challenge, acting on immunoregulatory switches that orchestrate immune effector functions may be an alternative, possibly more favourable approach.…”
Section: Gut Liver Axis and Systemic Inflammation In Alcoholic Liver Diseasementioning
confidence: 99%
“…Their function to limit excess inflammation physiologically mediates the balance between host immune competency and immunosuppression. A variety of genetic variants in immune checkpoint genes as well as pattern recognition receptor, cytokine, and other immune-related genes have been reported to significantly correlate to the clinical course or mortality of sepsis in the past years [15,16,21,24,25,43,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of the present study, we prospectively enrolled 707 consecutive patients with clinically defined sepsis from three surgical intensive care units (ICUs) at the University Medical Center Goettingen, Germany, since 2012. Our cohort of sepsis patients, or significant proportions of it, were previously studied in other published investigations for other clinical and experimental research questions by our study group [14][15][16]21,24,25,43]. Patient screening for sepsis and study recruitment was performed by study physicians on a daily basis using the currently valid international sepsis definitions and guidelines [1,[44][45][46].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…During sepsis‐induced acute lung injury, TIM‐3 + Tregs can upregulate the expression of IL‐4 and IL‐10 in a STAT‐3‐dependent manner [52]. Interestingly, it was found that due to a single nucleotide polymorphism, Tim‐3 may exert a differential influence on the clinical outcome of septic patients [53].…”
Section: Introductionmentioning
confidence: 99%